Transactional Relations Between Parenting Stress and Child Autism Symptoms and Behavior Problems - Rodriguez, Geovanna (J Autism Dev Disord, 2019)
Parents of children with autism spectrum disorder report elevated parenting stress. The current study examined bidirectional effects between parenting stress and three domains of child functioning (ASD symptoms, internalizing behavior problems, and externalizing behavior problems) across four time points in 188 families of children with ASD (ages 5–12 years). Mother and father reports of parenting stress and child functioning were used in cross-lag models to examine bidirectional associations between parenting stress and child functioning. Results indicated parent-driven effects for child internalizing behavior problems, while child externalizing behavior problems and ASD symptoms evidenced both parent-driven and child-driven effects, in different ways for mothers versus fathers. Overall, findings have important implications for interventions for families of children with ASD.